Laparoscopy or laparotomy as the way of entrance in myoma enucleation - Cezar, Cristina; Becker, Sven; Di Spiezio Sardo, Attilio; Herrmann, Anja; Larbig, Angelika; Tanos, Vasilis; Torres-de la Roche, Luz Angela; Verhoeven, Hugo Christian; Wallwiener, Markus; Wilde, Rudy Leon de (Archives of gynecology and obstetrics, 2017)
PurposeUterine myomas are the main cause of benign uterine diseases in premenopausal women. Objective of the present paper is to investigate the current best treatment modalities of myomas, depending on age of the patient and her desire to preserve fertility, as well as on clinical presentation of this pathology, such as size, number, and location of fibroids and, furthermore, on surgical experience of the gynecologist.MethodsThe design of our work is a systematic literature review of existing studies, reviews, and meta-analysis conducted in PubMed and Cochrane Library to identify relevant literature. Commonly, the myomectomy is to be recommended in women desiring to preserve fertility when myomas are associated with symptoms such as excessive bleeding, pelvic discomfort, or palpable abdominally fibroids.SummaryThe decision of surgical approach for myomectomy should be individualized, depending on size and location, as well as on surgeon’s experience. The different modalities of myomectomy, laparoscopic, hysteroscopic, robotic-assisted, or laparotomic are in detail presented in the paper, according to Society of Obstetricians and Gynecologists of Canada (SOGC) clinical practice guidelines and taking into consideration possible concerns of myomectomy such as uterine rupture, development of adhesions, and myomas’ recurrence.